Library Databases in ADINET - Goria, Sunil; Kumar, S. (Journal of Information and Knowledge, 2000)
Discusses various profiles of hardware configuration, software, databases, document, services of member libraries of ADINET (Ahmedabad Library Network), Problems related to human resources and applications have been discussed. Finally, conclusion is drawn with the hope that ADINET will emerge as a solid Metropolitan Area Network.